Statistical study of penile cancer - Matsuo, Y (Hinyokika kiyo. Acta urologica Japonica, 1988)
Between 1961 and 1985, 44 cases of penile cancer were experienced at Gunma University Hospital. We statistically analyzed 42 of them. The average age was 56.9 years old, ranging from 28 to 86 years old. Interval from onset of the disease to first visit to our hospital ranged from 0 to 50 months, averaging 9 months. The main chief complaints were mass formation, spontaneous pain, ulceration, and abnormality of urinary stream. More than 75% of them had phimosis. Thirty-one percent had stage 1, 29% stage 2, 38% stage 3, and 2% stage 4 cancer, according to Jackson's classification. All of them were diagnosed with squamous cell carcinoma. Surgical treatment was given to 37 patients (radical or partial penectomy was performed in most cases). Chemotherapy was given to 23 patients (main chemotherapeutic agent was bleomycin or peplomycin) and irradiation to 26 patients. Five-year survival was seen in 77% of the cases, 92% in low stage group (stage 1 and 2) and 63% in high stage group (stage 3 and 4). Ten-year survival was seen in 62% of the cases, 79% in low stage group and 43% in high stage group (Kaplan-Meier method)